Analisis Konsep Ultimum Remidium Terhadap Rekonstruksi Sistem Pemidanaan dalam Undang-Undang Perpajakan - Khalimi Khalimi (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2021)
Implementation of criminal sanctions in the Act No. 28 Year 2007 on General Rules of Taxation, give rise to legal issues in conceptual level. That the Tax Law, is a part of the State Administration Law, requiring forceful measures for taxpayers, especially the Taxable Entrepreneur, which in principle is a form of criminalization of administrative behavior. Criminal Law, through the principle of legality, wants a norm setting strict sanctions and obviously in the legislation, it appears to be broken in the Act No. 28 Year 2007 on General Rules of Taxation. Parameters of the crime of taxation is limited only by the elements of negligence and intentional, with the implementation under based on discretion of of the competent institution. Thus, gave rise the transactional behavior in a practical level. Therefore, the principle of ultimum remedium, becomes extremely important to avoid the use of arbitrary of discretion.